ANALISIS KUALITAS PELAYANAN VAKSINASI COVID-19 TERHADAP KEPUASAN PESERTA VAKSINASI DI PUSKESMAS LIRIK KABUPATEN INDRAGIRI HULU - Hanna Zarah Natasya; Bobi Handoko; Marian Tonis (LPPM Universitas Awal Bros, 2022)
In Indonesia, the implementation of vaccination has been carried out according to presidential instructions through Presidential Decree No. At Pukesmas Lirik Indragiri Hulu Regency, the implementation of the Covid-19 vaccination has been carried out, but there are still complaints about the registration flow, waiting room, queues that are not in accordance with arrivals and have not prioritized the elderly in queues and post-vaccination administration that is not in line with the queue. The purpose of the study was to determine the performance of officers, the level of satisfaction of Covid-19 vaccination patients, and the effect of service quality and patient satisfaction. This research uses quantitative research with descriptive method, conducted at Puskeamas Lirik Indragiri Hulu Regency with 98 respondents, namely patients who have vaccinated adults 26-45 years. The research was carried out by observation, data collection, and questionnaires. Data analysis in this study used univariate analysis, bivariate analysis, validity test, reliability test, normality test, and linearity test. Data processing using SPSS 16.0 data processing application. The results obtained based on the data processing in this study indicate that the quality of service has a positive and significant effect on patient satisfaction which is strengthened by the test results which show that it is supported by the linearity test which produces a linearity significance value of 0.000 < 0.05 obtained from data processing through the application SPSS 16.0 .